2017
DOI: 10.1097/md.0000000000006875
|View full text |Cite
|
Sign up to set email alerts
|

Continuous venovenous hemofiltration in the management of paraquat poisoning

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
13
0
6
Order By: Relevance
“…It has been suggested that removal of paraquat from the blood with hemoperfusion provides better clearance of paraquat than hemodialysis, and that the use of hemoperfusion within 12 hours of poisoning may reduce mortality [15]. CVVH may improve survival, reduce organ dysfunction, and prolong the survival time for patients to receive additional treatments [16][17][18][19]. In one study, survival rates for patients who received early hemoperfusion were more than double those who did…”
Section: Removal Of Paraquat From the Bloodmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that removal of paraquat from the blood with hemoperfusion provides better clearance of paraquat than hemodialysis, and that the use of hemoperfusion within 12 hours of poisoning may reduce mortality [15]. CVVH may improve survival, reduce organ dysfunction, and prolong the survival time for patients to receive additional treatments [16][17][18][19]. In one study, survival rates for patients who received early hemoperfusion were more than double those who did…”
Section: Removal Of Paraquat From the Bloodmentioning
confidence: 99%
“…-HP results in a more rapid reduction of paraquat plasma and early initiation can be predictive of survival [18,23] -CVVH may prolong the survival time for patients to receive additional treatments [16,17] Study Type(s): Reference(s):…”
Section: Hemoperfusion Hemodialysis and Cvvhmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there are five meta-analyses about treatment of PQ poisoning. [1516171819] Agarwal et al ., Li et al ., and He et al . reported meta-analysis about the effect of pulse immunosuppressive and glucocorticoid therapy, which showed a beneficial effect.…”
Section: Introductionmentioning
confidence: 99%
“…[151618] CVVH prolonged the survival time of the patients without significant effect on mortality. [19] Li et al . reported a meta-analysis about the reducing effect of HP on mortality.…”
Section: Introductionmentioning
confidence: 99%